MODEL LAYANAN CLOUD COMPUTING PADA SISTEM PENYEDIA UJIAN SEKOLAH DASAR - Rifky Lana Rahardian; Wayan Andrika Putera; Kelsen Kelsen (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
In practice, the application of technology in elementary schools is still very minimal. The process of daily exams or tests still uses a lot of paper which can endanger nature globally because cutting down trees is used as a basic ingredient in making paper. What's more, elementary schools are different from tertiary institutions which have a greater investment value in their business processes, so that elementary schools still maintain conventional school administration processes and have not yet implemented technology to support school administration processes and improve work efficiency. Currently the world is in a post-pandemic condition, where previously when the pandemic took place schools were conducted online. This shows the readiness of which schools are able to adapt quickly to a condition and seek technological solutions to support their business processes. Technology is considered important by parents today because with the existence of technology the teaching and learning process can always be handled properly and more efficiently. We need a system that can handle the problems that exist in SD by utilizing SAAS (Software As A Service) based Cloud Computing service technology. With the existence of this Cloud Computing service model, in the future it will not only become a place for many SDs but will become a business environment.